Genuine redundancy and retrenchment compensation: an analysis of Malaysian law - Ali Mohamed, Ashgar Ali; Eishan Jan, Mohammad Naqib; Ahmad, Muhamad Hassan; Kasi, Arun (International Organization Center of Academic Research (OCERINT), 2018)
Retrenchment is a process to discharge the surplus labour arising due to various factors which renders the services of the redundant worker no longer needed by the employer. This might happen firstly, when the business itself ceases to operate or the business no longer exists, secondly, when the place where the employee was contracted to work disappears, thirdly, the job itself disappears and fourthly, when less employees are needed to do the same job while the job still exists. All these are brought about because of change in business as times are not always booming in the business world. In a genuine redundancy situation, it is pertinent for the employer to pay retrenchment benefits or compensation to the affected workers in order that they are able to cope with immediate aftermath of retrenchment. The retrenchment payment is a minimum sum paid to the employee based on the length of service for loss of the job. Having said the above, this paper will seek to discuss genuine redundancy and the retrenchment compensation with reference to the law and practice in Malaysia. Here, unlike some developed countries such as the United Kingdom, not all workers will be eligible for the compensation in the event their services are no longer required by the organisation due to genuine redundancy in the organisation. Hence, this paper will, apart from discussing what it means by ‘genuine redundancy’ and ‘retrenchment compensation’ from the Malaysian perspective, will also propose reform of the existing law to accord retrenchment compensation to all workers affected by the retrenchment.